The Impact of Business Process Re-engineering on the Performance of Government Organizations and Achieving the Kingdom’s 2030 Vision: A Field Study on the Employees of the Ministry of Justice in Makkah Al-Mukarramah Region Branch of Administrative, Financ - AlQurashi, Suzan; Alsolami, Nahr (The Arab Journal of Administration, 2022)
The present study aimed to identify the actual impact of the re-engineering of administrative processes on institutional performance in the Ministry of Justice in Jeddah. In order to achieve the aims of the study the researcher used the descriptive methodology, and designed a questionnaire and the interview by E-mail, in view of the Corona pandemic, the study community consists (3000) employees working in the Ministry of Justice and the administrative and financial courts, according to the statistics received from the Director of Human Resources and The sample (341) and the respondents (168) . The data of this study were analyzed using (SPSS) version (24), and an Excel program was also used to create graphs. The most important results the study has reached are: 1- Acceptance of the first hypothesis, which states that: There is a strong positive effect to simplify work procedures in the ministry on the quality of service provided in the ministry. 2- Accepting the second hypothesis, which states that: There is a strong positive effect to improve the image of the ministry’s workers on the quality of service provided in the ministry. 3- Acceptance of the third hypothesis, which states that: There is an average positive effect of The success factors of re-engineering administrative processes in the ministry on the quality of service provided in the ministry. 4- Rejection of the sixth hypothesis, there are no differences on the application of re-engineering of administrative processes and performance in the Ministry of Justice in Jeddah due to the demographic factors of the study sample. This study presented recommendations for adopting the administrative re-engineering process approach as one of the tools for change in developing the administrative work in the Ministry of Justice, and enhancing the concept of administrative process engineering among the Ministry of Justice employees.